Capacity for Self-Control and Individuals' Interest in Exercising Self-Control - Tittle, Charles R. (Journal of quantitative criminology, 2004)
We identify and elaborate a conceptual distinction between capability for self-control and the desire to exercise it, and employ data from a city survey to explore the empirical viability of such a differentiation. Separate scales measuring ability and desire to exercise self-control both prove to be significant and moderately strong predictors of several measures of criminal/deviant behavior, showing independent, cumulative, and interactive relationships with each other. For some measures of crime/deviance, self-control capability is most effective when the individual's interest in exercising self-control is low but its effect is greatly reduced or eliminated when desire to exercise self-control desire is high. Combinations of capability for self-control and interest in exercising it prove to be particularly good predictors of the absolute level of misbehavior.